Visualizing emotions in the Ancient Near East (Leuven ; Paris ; Bristol)
viii, 293, [8] sayfa
Keywords: “The history of emotion is an important interdisciplinary research field, not least because it touches fundamental questions about the distinction between psychobiology-based universals und socio-cultural, path-dependent and thus relative peculiarities. Conceptual incongruities between what is today understood as emotion and various views on emotions in antiquity should not distract from the fact that, while emotions do have history, they substantially belong to all human experience as such. Visual media and images open perspectives for transcultural research that differ from the testimony of texts. Their study can thus make a major contribution to a better understanding of emotions in the Ancient Near East. How where gestures, body postures, facial expressions etc. visualized in images from Mesopotamia, the Levant and Egypt and what role does the visualization play in communicating emotions? The first part of the present volume takes concrete examples as a starting point and discusses the fundamental question whether or not emotions were represented and can thus be studied in Ancient Near Eastern art. Approaches and arguments are controversial: Some authors argue that there are no visualizations of emotions, but only of cultural roles and ritual embodiments. Their view is contrasted by other contributors, who assume that one may detect non-verbal expressions hiding emotions in visual representations and that it is crucial to specify the appropriate tools and methodologies to interpret them in an adequate way. The second part offers five additional theoretical reflexions from comparative, linguistic and art-historical perspectives. With such a broad interdisciplinary approach including Assyriology, Egyptology, Near Eastern archaeology and Hebrew Bible/Old Testament studies, the volume offers a large panorama of the most important research positions on a fundamental topic.” --